Myopathy Associated With Dermatan Sulfate-Deficient Decorin and Myostatin in Musculocontractural Ehlers-Danlos Syndrome: A Mouse Model Investigation - Nitahara-Kasahara, Yuko; Posadas-Herrera, Guillermo; Mizumoto, Shuji; Nakamura-Takahashi, Aki; Inoue, Yukiko U.; Inoue, Takayoshi; Nomura, Yoshihiro; Takeda, Shin’ichi; Yamada, Shuhei; Kosho, Tomoki; Okada, Takashi (Frontiers in Cell and Developmental Biology, 2021)
Carbohydrate sulfotransferase 14 (CHST14) encodes dermatan 4-O-sulfotransferase 1, a critical enzyme for dermatan sulfate (DS) biosynthesis. Musculocontractural Ehlers-Danlos syndrome (mcEDS) is associated with biallelic pathogenic variants of CHST14 and is characterized by malformations and manifestations related to progressive connective tissue fragility. We identified myopathy phenotypes in Chst14-deficient mice using an mcEDS model. Decorin is a proteoglycan harboring a single glycosaminoglycan chain containing mainly DS disaccharides, which are replaced with chondroitin sulfate (CS) in mcEDS patients with CHST14 deficiency. We studied the function of decorin in the skeletal muscle of Chst14-deficient mice because decorin is important for collagen-fibril assembly and has a myokine role in promoting muscle growth. Although decorin was present in the muscle perimysium of wild-type (Chst14+/+) mice, decorin was distributed in the muscle perimysium as well as in the endomysium of Chst14-/- mice. Chst14-/- mice had small muscle fibers within the spread interstitium; however, histopathological findings indicated milder myopathy in Chst14-/- mice. Myostatin, a negative regulator of protein synthesis in the muscle, was upregulated in Chst14-/- mice. In the muscle of Chst14-/- mice, decorin was downregulated compared to that in Chst14+/+ mice. Chst14-/- mice showed altered cytokine/chemokine balance and increased fibrosis, suggesting low myogenic activity in DS-deficient muscle. Therefore, DS deficiency in mcEDS causes pathological localization and functional abnormalities of decorin, which causes disturbances in skeletal muscle myogenesis.